Running periodization - adapted from running periodization: training theories to run faster - Part 2: reverse linear periodization - Karp, J. (Techniques Magazine, 2023)
Historically, linear periodization was designed to improve strength, speed, and power, and so the training progressed from general conditioning (volume) to specific skills (intensity), with the highest intensity coming at the end of the training program. Reverse linear periodization takes the opposite approach of linear periodization - a gradual and progressive increase in volume and decrease in intensity.